POLITICAL AND LEGAL PRINCIPLES OF PUBLIC-PRIVATE PARTNERSHIP IN THE FIELD OF CULTURE IN UKRAINE - Yeromina , O. (Theory and Practice of Public Administration, 2020)
The article analyzes the main political and legal principles of public-private partnership in the field of culture in Ukraine and explore the mechanism of public-private partnership in the formation and implementation of cultural policy.Democratic countries experience convincingly shows that the cultural policy is effective in the conditions of involving the general public in its development and implementation. Due to the combination of state and public elements of governance in the field of culture public policy becomes balanced, transparent and effective. It should be pointed out that world practice of efficient governance uses partnership of government agencies and various public, non-governmental, non-profit, charity, business organizations and foundations interested in solving the problems of cultural development. Sustainable partnerships between public and private representatives is complicated by underdeveloped economic and institutional basis, redistribution of proprietary, incompetence of management decisions concerning to public-private partnerships. There is also a lack of clear understanding of the specific characteristics of its models, implementation mechanisms and potential risks that lead to inefficient use of investment resources and loss of business interest in participating in public-private partnerships.During our research, the foreign experience of involving the private sector in solving problems of social development has been analyzed. The meaning of public-private partnership in the field of culture is revealed. Forms and stages of public-private partnership are indicated. It is marked down that during formation and implementation of public-private partnership in the field of culture its features should be primarily considered. The sectoral distribution of public-private partnership agreements in Ukraine as of January 1, 2020 is given. It was revealed that the implementation of public-private partnership projects in the social sphere is not popular among domestic investors.